Customers' attitude toward online shopping - Chong, Wen Jun (2016)
Internet has become increasingly popular. Online shopping is a business medium for transactions among entrepreneurs and customers. As a new channel for marketing, online shopping played a significant role. It provides satisfaction for customers seeking convenience and speed when they purchase products. Customers’ online shopping attitudes refers to customers’ psychological state of decision making on internet, and customers’ attitudes will affect customers’ intention to make purchases online. Therefore, understanding the behaviour of the consumers, what they buy from online shops, why they choose online shopping becomes a vital issue for online entrepreneurs. The scope of this study is to examine the factors influenced on customers’ attitudes towards online shopping in terms of customers’ shopping orientation, website quality and psychological perception. This study comprised of respondents who are graduate students in University Utara Malaysia and Qin Hai University of China. The study shows that the three independent variables have significant influence on customers’ attitudes towards online shopping.